A new meandered-stripline fed dual band patch antenna - Ahsan, M.R.; Islam, M.T.; Ullah, M.H. (Applied Computational Electromagnetics Society Journal, 2015)
A new circular shaped patch antenna loaded with vertical slots and fed by meandered-stripline on a high dielectric material substrate is proposed in this paper, and experimentally verified the performance of the printed prototype. With the deployment of meandered-stripline structure to excite in the assistant of partial ground plane, the experimental results show that the proposed antenna has achieved wider bandwidth with satisfactory gain. The measured impedance bandwidth (voltage wave stand ratio, VSWR <= 2) of the proposed antenna at lower band is 400 MHz (600 MHz - 1 GHz) and at upper band is 700 MHz (2.25 GHz - 2.95 GHz). The peak gains of -1.18 dBi and 4.87 dBi have measured with topmost radiation efficiencies of 82.0 and 92.6 and have observed at lower band and upper band respectively. The performance criteria and almost consistent radiation pattern make the proposed antenna as a suitable candidate for UHF RFlD, WiMAX and WLAN applications. The designing of antenna model and the parametric study have been performed with commercially available EM simulation software on 64-bit windows PC. The proposed antenna model has been validated by comparing the obtained experimental results with the output from the numerical simulation and apparently shows good agreement between them.